Creation or evolution do we have to choose? - Alexander, Denis (Oxford ; Grand Rapids, Mich. : Monarch Books, 2008)
In this brilliant and highly readable treatise, Denis Alexander the scientist-believer argues convincingly and lovingly that a committed Christian need not fear evolution, but can embrace it as God's awesome means of creation.'
What do we mean by creation? -- The biblical doctrine of creation -- What do we mean byevolution?: Dating, DNA and genes -- What do we mean by evolution?: Natural selection and reproductive success -- What do we mean by evolution?: Speciation, fossils and the question of information -- Objections to evolution -- What about Genesis? -- Evolutionary creationism -- Who were Adam and Eve?: The background -- Who were Adam and Eve?: Genesis and science in conversation -- Evolution and the biblical understanding of death -- Evolution and the Fall -- Evolution, natural evil and the theodicy question -- Intelligent design and creation's order -- Evolution--intelligent and designed? -- The origin of life.
Includes bibliographical references (p. 355-368) and index.
Description based on print version record.
Keywords: Creationism; Evolution (Biology); Creation; Evolution (Biology) -- Religious aspects -- Christianity; RELIGION / Christian Theology / General; Electronic books